1996
DOI: 10.1364/ao.35.001950
|View full text |Cite
|
Sign up to set email alerts
|

Ellipsometry of diffractive insect reflectors

Abstract: Scales on the wings of certain insects, such as Trichoplusia orichalcea, exhibit a surface micro structure resembling a fine diffraction grating. Diffraction of incident light by this structure is responsible for many of the optical properties of the wings of this moth, such as the metallic yellow color and the almost-specular reflection and polarization properties of the scattered radiation. It is shown that by the use of null ellipsometry the polarization characteristics can be used to obtain the optical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Some early determinations of n and k of reflectors on insects using single-wavelength ellipsometry were performed by Brink and Lee [17]. They found N = 1.55 + i0.02 and N = 1.54 + i0.56 at a wavelength of 633 nm and 488 nm, respectively, in the metallic-like yellow moth Trichoplusia orichalcea.…”
Section: MMmentioning
confidence: 99%
See 1 more Smart Citation
“…Some early determinations of n and k of reflectors on insects using single-wavelength ellipsometry were performed by Brink and Lee [17]. They found N = 1.55 + i0.02 and N = 1.54 + i0.56 at a wavelength of 633 nm and 488 nm, respectively, in the metallic-like yellow moth Trichoplusia orichalcea.…”
Section: MMmentioning
confidence: 99%
“…Later, the same group determined the low and high index in a thin film multilayer stack in the moth Chrysiridia croesus which exhibits green, purple and orange-pink colors [18]. Using the same technique as in [17], they found indices of the order of 1.63 and 1.74 for the low-and high-index layers, respectively, and also concluded that these layers essentially were non-absorbing (k = 0). These data were used with neglected dispersion to simulate reflectance spectra.…”
Section: MMmentioning
confidence: 99%
“…However, ellipsometry has rarely been used on natural nanostructures. Early work by Brink and Lee [23] demonstrated that optical constants of scale material on wings of insects may be determined using null ellipsometry.…”
Section: Introductionmentioning
confidence: 99%
“…It can even give access to more information on the structure, here geometrical information through the tilt angle and optical information through the thickness and refractive index of the optically equivalent layer (see also Ref. [9]). …”
Section: Interferencementioning
confidence: 99%